Misconduct by police leaders in England and Wales: an exploratory study - Hough, Mike (Policing and society, 2018)
The study that this article is based on examined cases of alleged misconduct involving chief police officers and staff. It described the nature of cases that came to light, examined pathways that lead to misconduct, and suggested ways of mitigating risks. The study was based on interviews with key stakeholders and with investigating officers in chief officer misconduct cases since April 2008. Cases involving chief officer misconduct fell into two broad categories: those associated with professional decision-making and those related to interpersonal conduct. In around a third of cases, no misconduct was found. There were various routes into misconduct. The ethical climate of a police force was a key determinant of chief officer misconduct. Behaviour was also shaped by individual vulnerabilities, including lack of support, lack of challenge, exposure to corrupting influences, and cognitive failures in decision-making. Various things can be done to mitigate the risk of chief officer misconduct: police leadership needs to develop a greater consensus on what constitutes misconduct; chief officers need to recognise the specific risks of cognitive failure that organisational leaders face, and the temptations of excepting themselves from rules and norms. There also needs to be an organisational ethos in which leaders can be challenged and in which leaders are given the right sort of support when faced with ethical challenges. There needs to be more recognition of the impact of selection and training processes, and of performance management systems, on the ethical climate of police organisations.